Delirium in Older Patients With COVID-19: Prevalence, Risk Factors, and Clinical Relevance. (4th February 2021) - Mendes, Aline; Herrmann, François R; Périvier, Samuel; Gold, Gabriel; Graf, Christophe E; Zekry, Dina
Abstract: Background: Delirium prevalence increases with age and is associated with poor outcomes. We aimed to investigate the prevalence and risk factors for delirium in older patients hospitalized with COVID-19, as well as its association with length of stay and mortality. Method: This was a retrospective study of patients aged 65 years and older hospitalized with COVID-19. Data were collected from computerized medical records and all patients had delirium assessment at admission. Risk factors for delirium as well as the outcomes mentioned above were studied by 2-group comparison, logistic regression, and Cox proportional hazard models. Results: Of a total of 235 Caucasian patients, 48 (20.4%) presented with delirium, which was hypoactive in 41.6% of cases, and hyperactive and mixed in 35.4% and 23.0%, respectively. Patients with cognitive impairment had a nearly 4 times higher risk of developing delirium compared to patients who were cognitively normal before SARS-CoV-2 infection (odds ratio 3.7; 95% CI: 1.7–7.9, p = .001). The presence of delirium did not modify the time from symptoms' onset to hospitalization or the length of stay in acute care, but it was associated with an increased risk of dying (hazard ratio 2.1; 95% CI: 1.2–3.7, p = .0113). Conclusion: Delirium was a prevalent condition in older people admitted with COVID-19 and preexisting cognitive impairment was its main risk factor. Delirium was associated with higher in-hospital mortality. These results highlight the importance of early recognition of delirium especially when premorbid cognitive comorbidities are present.